Role of speciality corn and their specific production technologies to enhance farmers’ income - BAJPAI, RAMAKANT; GOSWAMI, R G (Indian Farming, 2018)
Compared to field corns, specialty corns possess additional and characteristic features. Their global spread, increasing demand and premium price make them an attractive option for the farmers in many foreign countries including India. Specialty corns are amenable to numerous options pertaining to harvest time and various economical products.